Engineering and targeting potential of CAR NK cells in colorectal cancer - Muhammad Babar Khawar; Ali Afzal; Shuangshuang Dong; Yue Si; Haibo Sun; Yuanyuan Ji (Chinese Medical Journal)
Abstract. Colorectal cancer (CRC), a major global health concern, necessitates innovative treatments. Chimeric antigen receptor (CAR) T cells have shown promises, yet they grapple with challenges. The spotlight pivots to the rising heroes: CAR natural killer (NK) cells, offering advantages such as higher safety profiles, cost-effectiveness, and efficacy against solid tumors. Nevertheless, the specific mechanisms underlying CAR NK cell trafficking and their interplay within the complex tumor microenvironment require further in-depth exploration. Herein, we provide insights into the design and engineering of CAR NK cells, antigen targets in CRC, and success in overcoming resistance mechanisms with an emphasis on the potential for clinical trials.